Experiment on steel fibre reinforced end anchorage - Teo, Shi Lan. (2010)
This report involves the research on the failure mode of Steel Fibre Reinforced End Anchorage. Both experimental and analytical components are involved in this research. The experimental component of this project requires testing of eight specimens to failure. The dimensions of all the specimens were approximately 275mm x 700mm x 700mm. Steel Fibres were uniformly distributed in all specimens at 40kg per cubic metre. The average groove width of four specimens is 143mm and 91mm for the other four specimens. The eccentricities for the experiment ranges from 32.5mm to 38mm.The specimens were casted in three different batches. Hence, compressive cube strength test and splitting cylinder test were carried out for all three batches. All specimens were tested after 28 days of curing. The specimens were tested using the Universal Testing Machine RBU 5000 with a capacity of 5000KN. The six specimens which were loaded fully wedge beneath the bearing plates. Tensile cracks were observed beyond the wedging. For the other two specimens, tensile cracks were observed at the side of the specimens. With regards to analytical works, an excel spreadsheet was developed based on the Strut-and-Tie Truss model to predict the ultimate failure load. In this project, an equation to predict the ultimate load was formulated from the current Strut-and-Tie Truss model. The formulated equation provides underestimation of the ultimate load of the specimens. Recommendation was proposed with regards to changing the dimension of the truss model. The proposed model took into consideration of the difference in the width of loading area and the eccentricity present. Thus, the proposed truss model provides better correlation between the predicted and experimental ultimate load.